The benefits of healthy eating during the COVID-19 pandemic (Research, Society and Development, 2022)
The current work aims to evaluate the benefits of healthy eating in the midst of the COVID-19 pandemic, seeking to highlight care and its benefits for health promotion. Through an integrative literature review with a qualitative approach, the Scientific Electronic Library Online (SCIELO), MEDLINE/PUBMED and Latin American Caribbean Literature on Health Sciences (LILACS) databases were used, in a time frame between 2012 and 2022 , Therefore, the importance of this subject was verified, since a balanced diet that offers important nutrients for the proper functioning of the body can boost our immune system to fight foreign bodies, the pandemic scenario generated by COVID-19 reinforced the need for public policies that minimize the food and nutrition insecurity of marginalized families. It is known that foods provide us with essential nutrients for strengthening the immune system, among these studies they mention: Vitamin A, Vitamin C, Vitamin D, Vitamin E, Zinc, Selenium, Iron and Magnesium. Therefore, in times of a pandemic, eating healthy is essential. In this sense, the choice of food ingested should prioritize the nutrients present in the food.